2019
DOI: 10.1108/jhlscm-01-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Developing and analyzing framework to manage resources in humanitarian logistics

Abstract: Purpose Humanitarian services usually perform in the face of uncertainty in which mobilization of resources in an efficient and effective manner is a big challenge. Sharing timely and correct information among logistics partners and workers is a key to drive rapid response logistics effectively. The purpose of this paper is to understand how coordinated effort effects resources management (RM). Design/methodology/approach This study uses quantitative research methodology and collected data from 82 humanitari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 106 publications
(177 reference statements)
1
13
0
Order By: Relevance
“…Last, the robustness and quality of data was evaluated by assessing the causality by the help of nonlinear bivariate causality direction ratio (NLBCDR) as discussed by Kock (2018). The value exceeding 0.7 justifies the absence of endogeneity which in the represent study is found close to 1 (Ahmed et al, 2019b). Thus all of these tests confirms the absence of the aforementioned biases and hence favored the application of PLS-SEM.…”
Section: Methodssupporting
confidence: 77%
“…Last, the robustness and quality of data was evaluated by assessing the causality by the help of nonlinear bivariate causality direction ratio (NLBCDR) as discussed by Kock (2018). The value exceeding 0.7 justifies the absence of endogeneity which in the represent study is found close to 1 (Ahmed et al, 2019b). Thus all of these tests confirms the absence of the aforementioned biases and hence favored the application of PLS-SEM.…”
Section: Methodssupporting
confidence: 77%
“…An area where performance management has witnessed considerable growth in attention is humanitarian supply chain management (Ahmed et al, 2019). This type of supply chain management deals with the coordination and integration of external stakeholders in a relief chain to rapidly provide humanitarian assistance to areas affected by large-scale emergencies (Cozzolino, 2012).…”
Section: Humanitarian Vs Business Supply Chainsmentioning
confidence: 99%
“…The existing research identified various causes of corruption in the developing countries, as discussed in the preceding paragraphs and enumerated various recommendations to encounter corruption and incorporate transparency in humanitarian logistics and supply chains (Ahmed et al, 2019;Francis and Armstrong, 2011;Maxwell et al, 2012). Illegal appointments, misuse of resources, unfair distribution, low quality, embezzlement of funds and influence of local people are some of the main causes of corruption and ineffective disaster relief management in humanitarian logistics in countries like Pakistan (Ahmed et al, 2019). Towards, the solution, Transparency International (2021), in its handbook, presented the remedy for preventing corruption in humanitarian logistics.…”
Section: Transparencymentioning
confidence: 99%
“…The existing research identified various causes of corruption in the developing countries, as discussed in the preceding paragraphs and enumerated various recommendations to encounter corruption and incorporate transparency in humanitarian logistics and supply chains (Ahmed et al. , 2019; Francis and Armstrong, 2011; Maxwell et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation